Interleukin-10 receptor signaling promotes the maintenance of a PD-1int TCF-1+ CD8+ T cell population that sustains anti-tumor immunity - Hanna, Bola; Llaó Cid, Laura; ̇Iskar, Murat; Rößner, Philipp M.; Klett, Lara C.; Wong, John K. L.; Paul, Yashna; Ioannou, Nikolaos; Öztürk, Selcen; Mack, Norman; Kalter, Verena; Colomer, Dolors; et al. (Immunity, 2021)
T cell exhaustion limits anti-tumor immunity and responses to immunotherapy. Here, we explored the microenvironmental signals regulating T cell exhaustion using a model of chronic lymphocytic leukemia (CLL). Single-cell analyses identified a subset of PD-1hi, functionally impaired CD8+ T cells that accumulated in secondary lymphoid organs during disease progression and a functionally competent PD-1int subset. Frequencies of PD-1int TCF-1+ CD8+ T cells decreased upon Il10rb or Stat3 deletion, leading to accumulation of PD-1hi cells and accelerated tumor progression. Mechanistically, inhibition of IL-10R signaling altered chromatin accessibility and disrupted cooperativity between the transcription factors NFAT and AP-1, promoting a distinct NFAT-associated program. Low IL10 expression or loss of IL-10R-STAT3 signaling correlated with increased frequencies of exhausted CD8+ T cells and poor survival in CLL and in breast cancer patients. Thus, balance between PD-1hi, exhausted CD8+ T cells and functional PD-1int TCF-1+ CD8+ T cells is regulated by cell-intrinsic IL-10R signaling, with implications for immunotherapy.
Gesehen am 02.03.2022
Im Titel sind "int" und "+" hochgestellt